Employee Performance: Organizational Culture, Occupational Health and Safety (K3), with Job Satisfaction as a Mediator: Kinerja Karyawan: Budaya Organisasi, Kesehatan dan Keselamatan Kerja (K3), dengan Kepuasan Kerja sebagai Variabel Mediasi. - Bagus Irawan; Sumartik (Academia Open, 2024)
The study aimed to explore the impact of organizational culture and occupational health and safety on employee performance and job satisfaction. Using a quantitative approach with 170 purposively sampled respondents, the research employed smartPLS for analysis. Findings revealed a positive influence of organizational culture on performance and job satisfaction. However, occupational health and safety showed no direct impact on performance. Interestingly, organizational culture indirectly affected performance through job satisfaction as a mediating variable. Similarly, occupational health and safety influenced performance through job satisfaction. Overall, job satisfaction emerged as a key factor affecting employee performance. Highlights: Organizational Culture Impact: The study reveals a significant influence of organizational culture on employee performance, emphasizing the pivotal role that the workplace environment and values play in shaping individual effectiveness. Occupational Health and Safety Nexus: Interestingly, the research indicates no direct impact of occupational health and safety on employee performance. This finding prompts further exploration into the nuanced relationships between workplace safety measures and overall job effectiveness. Job Satisfaction as a Mediator: The study underscores the crucial role of job satisfaction as a mediator, demonstrating how it bridges the influence of organizational culture and health and safety measures to ultimately impact employee performance. This highlights the interconnected nature of workplace elements in shaping job satisfaction and, subsequently, performance. Keywords: Organizational Culture, Occupational Health and Safety (K3), Employee Performance, Job Satisfaction